ANALYSIS OF THE PENTAHELIX MODEL AND ITS IMPLICATIONS IN THE DEVELOPMENT OF SUSTAINABLE TOURISM IN GOA GIRI PUTRI TEMPLE, NUSA PENIDA - Ni Putu Sri Sujeni Setiawati; Ni Made Dwipayanti (Ride: Journal of Cultural Tourism and Religious Studies, 2025)
This research aims to identify and analyze key actors in the implementation of sustainable tourism at Goa Giri Putri Temple, Nusa Penida. As a religious tourism destination that continues to grow, Goa Giri Putri Temple faces challenges in maintaining a balance between tourist needs and preserving culture and the environment. A qualitative approach was used in this research, with data collection through in-depth interviews and observation. Several key actors involved in managing sustainable tourism in this area include local governments, temple managers, local communities and tourism industry players. The research results show that the role of local governments is very important in establishing regulations and building environmentally friendly infrastructure. Temple managers play a role in maintaining spiritual and cultural values, so that tourists can understand the importance of preserving local culture. Local communities play a role in supporting the tourism economy while protecting the environment, while tourism industry players assist in destination promotion and services to tourists by paying attention to sustainable practices. Strong collaboration and coordination between these actors is the main key in achieving sustainable tourism. This research concludes that a collaborative approach between the government, managers, community and tourism industry players is a determining factor in maintaining the sustainability of tourism at Goa Giri Putri Temple. It is hoped that this study can become a reference in developing sustainable tourism policies and practices in similar tourist destinations.